Financial well-being of Nigerian family in Ikeja Lagos State Nigeria - Christianah, Ogunleye Kemisola; Sabri, Mohamad Fazil; Zainal Badari, Shamsul Azahari (Shanlax International Journals, 2019)
With the recent advancement in the financial economy, it has become pertinent to families to be knowledgeable and adept in handling their finances. Financial markets terrain has increased so much, resulting in the availability of a more extensive choice of financial products and services, thus making financial decisions more complex and demanding. The ease of accessibility to inventive loans and credit services, financial market restructuring and technological advancements in the mode of offering and distributing financial services have indisputably left several individuals with a puzzling assortment of savings opportunities and decisions that need to be made. Therefore, this study was conceptualized to examine the factors that determine the financial well-being of Nigerian families in Ikeja local government, Nigeria. The researcher employed a stratified random sampling in selecting the number of employees, and 400 questionnaires were distributed to achieve a reasonable responses rate. As such, eighty (80) questionnaires were distributed to each of the five departments selected. From the study, it was shown research showed that majority of the respondents were female between the age ranges 20 to over 60 years. Results of the study showed that there was a significant relationship between financial well-being and financial management and financial strain expect for financial literacy. The regression analysis showed that the factors (financial literacy, financial stress, and business management) jointly for 45.7% of the variance in financial well-being. It was suggested that to improve economic prosperity among the employees in the local government, in Ikeja Lagos, Nigeria, an active factor is needed for family financial well-being.